TEACHER CAPACITY ENHANCEMENT IN THE IMPLEMENTATION OF STRENGTHENING CHARACTEREDUCATION THROUGH IN HOUSE TRAINING AT KRANGGAN STATE ELEMENTARY SCHOOL KAPANEWON GALUR - Eryati Mundilestari (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
This study aims to implement In House Training steps in an effort to improve teachers' abilities in implementing strengthening character education and increasing teachers' abilities in implementing strengthening character education through In House Training at Kranggan Kapanewon Galur Public Elementary School. This research was conducted at SD Negeri Kranggan Kapanewon Galur, Kulon Progo Regency. This research is a School Action Research. The research subjects were Class I-VI teachers at SD Negeri Kranggan Kapanewon Galur, Kulon Progo Regency. Research procedures through planning, implementation, observation or observation, and reflection. Data collection techniques through observation, documentation, field notes and research instruments. Data analysis techniques using qualitative analysis. The results of the study show that the In House Training steps to improve the ability of class teachers in implementing strengthening character education at SD Negeri Kranggan Kapanewon Galur are through a process of planning and implementing which has increased the success rate of 91,6% with category A in Cycle I and 100% with category A in Cycle II. Teacher's Ability to Apply Strengthening Character education increased by an average of 72.35% in Cycle I with category C, increased again to 86.5% in Cycle II with category B.